2023
DOI: 10.1021/acs.jpcb.3c00217
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Electrostatic Frequency Map for the NH Stretch of the Protein Backbone and Application to Chiral Sum Frequency Generation Spectroscopy

Abstract: We develop an electrostatic map for the vibrational NH stretch (amide A) of the protein backbone with a focus on vibrational chiral sum frequency generation spectroscopy (chiral SFG). Chiral SFG has been used to characterize protein secondary structure at interfaces using the NH stretch and to investigate chiral water superstructures around proteins using the OH stretch. Interpretation of spectra has been complicated because the NH stretch and OH stretch overlap spectrally. Although an electrostatic map for wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…We argued that this shift is due to significantly fewer backbone hydrogen bonds in LE 7 β compared to LK 7 β, which indicates weaker interstrand hydrogen-bonding interactions in LE 7 β, but we did not analyze the OH stretch components of the spectrum. 37 Figures 4b and 4c show that the first hydration shell and backbone water responses of LE 7 β are very different from those of LK 7 β, even though the systems appear similar. The OH stretch response of LE 7 β is both much smaller and somewhat blue-shifted compared to that of LK 7 β.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…We argued that this shift is due to significantly fewer backbone hydrogen bonds in LE 7 β compared to LK 7 β, which indicates weaker interstrand hydrogen-bonding interactions in LE 7 β, but we did not analyze the OH stretch components of the spectrum. 37 Figures 4b and 4c show that the first hydration shell and backbone water responses of LE 7 β are very different from those of LK 7 β, even though the systems appear similar. The OH stretch response of LE 7 β is both much smaller and somewhat blue-shifted compared to that of LK 7 β.…”
mentioning
confidence: 89%
“…In particular, our previous work showed that intermolecular coupling is critical to the modeling of the combined NH/OH stretch chiral SFG response of LK 7 β. 37 If intermolecular coupling is neglected, a downward-pointing peak (indicated by a dip) appears that is not found in the experimental spectrum (Figure 5a). Our previous work also showed that almost all of the OH stretch signal and the most relevant NH/OH couplings arise between the biomolecule and the first hydration shell.…”
mentioning
confidence: 95%
See 3 more Smart Citations